2012
DOI: 10.4028/www.scientific.net/amm.224.325
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Flow in the Vane-Type Surface Tension Tank: Drop Tower Test Results

Abstract: The paper studied capillary flow in asymmetry interior corner in the vane-type surface tension tank, and calculated it by analytical solution. Proposed a variable of equivalent corner angle to calculate the parameters of meniscus, and then analyze the capillary flow at asymmetry interior corner. A vane-type surface tension tank model is tested at drop tower to observe the capillary flow at asymmetry interior corner in microgravity condition. The test results are compared with analytical solution results to ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Bolleddula et al [19] investigated the capillary flow phenomena using drop towers and concluded that compound capillary flows occurred spontaneously and simultaneously over local and global length scales. Li et al [20] studied the capillary flow in an asymmetric interior corner in a vane-type surface tension tank. Zhuang et al [21] conducted an experiment on the fluid storage characteristic of a refillable reservoir in microgravity.…”
Section: Introductionmentioning
confidence: 99%
“…Bolleddula et al [19] investigated the capillary flow phenomena using drop towers and concluded that compound capillary flows occurred spontaneously and simultaneously over local and global length scales. Li et al [20] studied the capillary flow in an asymmetric interior corner in a vane-type surface tension tank. Zhuang et al [21] conducted an experiment on the fluid storage characteristic of a refillable reservoir in microgravity.…”
Section: Introductionmentioning
confidence: 99%